Multiplikasi Tunas Belimbing Dewi (Averrhoa carambola) melalui Kultur In Vitro - Yati Supriyati; Ika Mariska; nFN Mujiman (Buletin Plasma Nutfah, 2006)
Star fruit (Averrhoa carambola) is one of tropical fruits which had a high content of vitamin C, which was higher than that in apple and grape. As fresh consumption, star fruit had a good role in decreasing human blood pressure. Main constraints of star fruit development weather for conservation purpose and or for cultivation were still limited due to lack of seedlings availability. In vitro culture technique was one of the altrnative technologies capable of producing seedlings in a large quantity, uniform growth and relatively in a short period. One of the important keys in micropropagation work was the step of shoot initiation and multiplication. In this study we used two kind of explant, namely shoot with single node and shoot from germinated embrio. Experiment I, shoot with single node and shoot from germinated embrio were planted at WPM media + citric acid 100 mg/l. The next activities was focused on single node shoots which was subcultured at WPM + BAP 0.5 mg/l. In experiment II in vitro shoots from previous experiment was subcultured at WPM + BA (1 and 2 mg/l) + thidiazuron (0.1 and 0.2 mg/l). To stimulate shoot multiplication rate, shoot was subcultured at WPM or MS media in combination with IAA 0.5 mg/l and zeatin 2 mg/l. To improve vigourity of the plant, in vitro shoots resulted from multiplication media was planted at WPM or MS media containing paclobutrazol (0.4 and 0.8 mg/l) + BA 2 mg/l + thidiazuron 0.2 mg/l. Result showed that the use of single node shoot as an explant better than shoot comes from germinated embrio. Sub culture of star fruit shoot on WPM basal media containing BAP of 0.5 mg/l produce the shoot number about 4, and the shoot number could be increased until 18 by using IAA 0.5 mg and zeatin 2 mg/l. The treatment of schock temperature at 4-5oC during 4 days before planting could fasten shoot initiation time from 3 months to 1 months. An addition of 0.4 mg/l paclobutrazol on MS or WPM media containing 2 mg/l BA and 0.2 mg/l thidiazuron could improve vigourity of plantlet. AbstrakBelimbing (Averrhoa carambola) merupakan tanaman buah tropik yang mengandung vitamin C lebih tinggi daripada apel dan anggur. Buah belimbing segar sangat berguna untuk menurunkan tekanan darah. Pengembangan tanaman ini untuk keperluan budi daya ataupun untuk tujuan konservasi masih belum optimal karena terbatasnya bibit. Teknik kultur jaringan merupakan alternatif teknologi yang mampu menyediakan bibit secara massal, seragam, dan relatif cepat. Salah satu tahap yang harus ditempuh dalam perbanyakan bibit melalui kultur jaringan adalah multiplikasi tunas yang menjadi kunci dalam keberhasilan teknik perbanyakan ini. Percobaan terdiri atas beberapa kegiatan menggunakan dua jenis eksplan, yaitu tunas dengan nodus tunggal dan tunas dari perkecambahan embrio. Pada percobaan I eksplan tunas dengan nodus tunggal ditanam pada media WPM + asam sitrat 100 mg/l kemudian disubkultur pada media WPM + BAP 0,5 mg/l. Pada percobaan II, tunas in vitro disubkultur kembali pada media WPM + BA (1 dan 2 mg/l) + thidiazuron 0,1 dan 0,2 mg/l). Untuk lebih memacu tingkat pertunasan dilakukan subkultur kembali pada media WPM atau MS yang ditambah dengan IAA 0,5 mg/l dan zeatin 2 mg/l. Untuk meningkatkan ketegaran, tunas hasil multiplikasi ditanam pada media WPM atau MS + BA 2 mg/l + thidiazuron 0,2 mg/l dan paclobutrazol (0; 0,4; dan 0,8 mg/l). Hasil penelitian menunjukkan bahwa penggunaan eksplan tunas dengan nodus tunggal lebih baik dibandingkan dengan tunas yang berasal dari perkecambahan embrio. Subkultur yang dilakukan pada media WPM yang mengandung 0,5 mg/l BAP dapat menginisiasi dan menghasilkan rata-rata empat tunas. Subkultur tunas belimbing pada media MS + IAA 0,5 mg/l + zeatin 2 mg/l dapat memacu pembentukan tunas yang banyak, mencapai 18 buah. Penambahan paclobutrazol 0,4 mg/l ke dalam media MS atau WPM yang telah mengandung BA 2 mg/l dan thidiazuron 0,2 mg/l dapat memperbaiki ketegaran biakan.